2019
DOI: 10.1007/s11095-019-2651-2
|View full text |Cite|
|
Sign up to set email alerts
|

Tobramycin Clearance Is Best Described by Renal Function Estimates in Obese and Non-obese Individuals: Results of a Prospective Rich Sampling Pharmacokinetic Study

Abstract: Purpose Tobramycin is an aminoglycoside antibiotic of which the 24 h exposure correlates with efficacy. Recently, we found that clearance of the aminoglycoside gentamicin correlates with total body weight (TBW). In this study, we investigate the full pharmacokinetic profile of tobramycin in obese and non-obese individuals with normal renal function. Methods Morbidly obese individuals ( n = 20) undergoing bariatric surgery and non-obese healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…An AUC‐guided aminoglycoside dosing strategy has gained momentum in the literature, but implementation is hindered by operational barriers and lack of consensus on definitive AUC/MIC efficacy targets. Several AUC‐based dosing methods in obese patients has been suggested with use of first‐order PK equations (requiring bedside calculation) or nomograms, but require validation in a real‐world clinical setting 78–80 . The current standard remains to dose aminoglycosides on a mg/kg basis using AdjBW coupled with individualized TDM 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An AUC‐guided aminoglycoside dosing strategy has gained momentum in the literature, but implementation is hindered by operational barriers and lack of consensus on definitive AUC/MIC efficacy targets. Several AUC‐based dosing methods in obese patients has been suggested with use of first‐order PK equations (requiring bedside calculation) or nomograms, but require validation in a real‐world clinical setting 78–80 . The current standard remains to dose aminoglycosides on a mg/kg basis using AdjBW coupled with individualized TDM 9 …”
Section: Discussionmentioning
confidence: 99%
“…79 As such, the authors proposed a novel weightbased (using TBW), CKD-EPI-based gentamicin dosing strategy for obese patients >100 kg, with a suggested 25% dose reduction in ICU patients, to approximate exposures (median AUC 0-24 of 85.9 mg•h/L) as lean patients dosed 6 mg/kg. 79 Smit et al 80 as those were the values observed in the study participants. 80 Of note, the AUC target of 75 mg•h/L is thought to maximize the probability of effect versus toxicity for pathogens with MICs between 0.5 and 1 mg/L, but higher targets are likely needed for MICs between 2 and 4 mg/L.…”
Section: Gentamicin Tobramycin and Amikacinmentioning
confidence: 91%
See 2 more Smart Citations
“… 28 In contrast, for other renally excreted drugs such as tobramycin and vancomycin, increased clearance values were observed with increasing body weights, albeit to varying extents and using varying covariate functions. 29 , 30 Considering the second explanation, the organic cation transporter 2 (OCT2) has been shown to be increased in obese overfed mice and obese humans, and is associated with increased renal gentamicin tubular uptake. 31 Consequently, we anticipate that the increase in gentamicin clearance with obesity may be related to the increase in OCT2 transporters in the kidneys of obese individuals.…”
Section: Discussionmentioning
confidence: 99%